Pengaruh Penyuluhan Kader Santri Terhadap Peningkatan Pengetahuan, Sikap dan Praktik Pencegahan Penyakit Kulit pada Santri di Pondok Pesantren Putri "X" Yogyakarta Tahun 2012 - Nuruz Zahro AL-Jannah; Narto Narto; Adib Suyanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2012)
Skin diseases were the priority among health problems of Girl Moslem Boarding School (PondokPesantren Putri) X of Yogyakarta. To solve the problems, supported by the potentiality of the existence of eight santries (students) health cadres, a pre-test post-test with control designed experiment was conducted to understand the influence of health elucidation carried out by the students health cadre on the increasing knowledge, attitide and practice among other girl students on skin diseases prevention. The treatment and control groups, both were consisted of thirty students. The results showed that students which were counselled by the trained fellow health cadres, their scores of health knowledge, attitude and practice increased higher than those of the control group (P<0,001).